2021
DOI: 10.3390/coatings11050573
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of Fluorinated Silica Hybrid Barrier Layers on Flexible Polymeric Foil

Abstract: The reported work was focused on sol–gel-derived organically modified and fluorinated silica coatings deposited on elastic polymeric foil. The structure and topography of the coatings were tested by infrared spectroscopy and microscopic studies. The functional properties were determined using thermal analysis, surface analysis, and oxygen permeability tests. The barrier feature of the investigated materials against oxygen was correlated with the properties of the coatings. The hybrid (organic–inorganic) struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…This phenomenon is caused by the increased roughness on a hydrophobic surface that enhances air entrapment within the micro- or nano-structures, resulting in a lower penetration ability and free movement of the liquids; thus, the bacteria can be easily removed and detached from the surface [ 31 ]. Another similar study by Startek et al [ 32 ] reported that the deposition of SiO 2 with ten fluorinated carbons in the alkyl chain (-CF 10 ) using spin-coating method onto PET substrate exhibits R RMS and R a values of 63.1 and 78.3 nm, respectively and increases the WCA value to 113°. In order to achieve superhydrophobicity, an increase of surface roughness is needed to reach a higher R RMS value, as reported by Ozkan et al [ 33 ], who successfully fabricated a Cu-nanoparticles-coated polydimethylsiloxane (PDMS) substrate with WCA = 151° and R RMS = 230 nm.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This phenomenon is caused by the increased roughness on a hydrophobic surface that enhances air entrapment within the micro- or nano-structures, resulting in a lower penetration ability and free movement of the liquids; thus, the bacteria can be easily removed and detached from the surface [ 31 ]. Another similar study by Startek et al [ 32 ] reported that the deposition of SiO 2 with ten fluorinated carbons in the alkyl chain (-CF 10 ) using spin-coating method onto PET substrate exhibits R RMS and R a values of 63.1 and 78.3 nm, respectively and increases the WCA value to 113°. In order to achieve superhydrophobicity, an increase of surface roughness is needed to reach a higher R RMS value, as reported by Ozkan et al [ 33 ], who successfully fabricated a Cu-nanoparticles-coated polydimethylsiloxane (PDMS) substrate with WCA = 151° and R RMS = 230 nm.…”
Section: Discussionmentioning
confidence: 92%
“…As deposition of coating materials has been reported to affect surface topography [ 31 , 32 , 33 , 34 ], we performed AFM to analyze the roughness of our fabricated surface. As shown in Figure 2 G, on one hand, the deposition of SiO 2 onto PET substrate showed root-mean-square roughness ( R RMS ) and average roughness ( R a ) values of 82.50 ± 16.22 nm and 65.15 ± 15.26 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic absorption bands of the −CF 2 and −CF 3 groups can be distinguished in the 1120–1250 cm −1 region. [ 1,54–57 ] Stretching bands at 1231 and 1198 cm −1 are assigned to asymmetric ( ν normala (−CF 2 ) and ν normala (−CF 3 )) stretching modes, whereas bands at 1144 and 1134 cm −1 correspond to symmetric ( ν normals (−CF 2 )) stretching modes. [ 1,52,58 ] Characteristic Si–O–Si asymmetric stretching (( ν normala (OSi 2 )) modes are observed at 1113, 1063, and 1015 cm −1 , whereas a symmetric stretching (( ν normals (OSi 2 )) band is noted at 804 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The silica coatings pure and doped with different substance (fertilizer) could be easily produced by the sol-gel method. It is known that silica coatings show good adhesion to various materials (metallic substrate [ 37 ], textile fabrics [ 38 ], polymers [ 39 ], and others [ 40 ]), thereby the idea to apply them on seeds emerged. Reagents used in a sol-gel synthesis (silica precursor and water) as well as ethanol as a by-product, are not harmful to seeds, but the idea of using sol-gel coatings for seeds modifications is poorly presented in the literature.…”
Section: Discussionmentioning
confidence: 99%